The Standard for Allocating Zakat Social Funds as An Operational Expense of Nonprofit Organizations in Indonesia, Sudan and Algeria - Febriandika, Nur Rizqi; Rohmah, Fatihah Annisa (Sekolah Tinggi Agama islam Negeri Majene, 2024)
Zakat in the socio-economic structure of society needs to be managed productively and professionally so that it leads the welfare of society. This study aims to reveal standards for the allocation of zakat social funds as an operational expense for nonprofit organizations. This research uses a descriptive qualitative type. We analyse secondary data retrieved in nonprofit organizations in three different countries (Indonesia, Sudan and Algeria). The result of the study revealed that Indonesia has two types of zakat management institutions, the National Amil Zakat Agency (BAZNAS) and Amil Zakat Institute (LAZ). Furthermore, Sudan possesses the Sudanese Zakah Chamber (SZC) or the Zakat Council and Algeria has Kotak Zakat. The pattern of zakat collection in Indonesia applies payments with a voluntary principle, however the zakat has been integrated with taxes so that they can submit claims for zakat payments. In Sudan, payments are made on the principle of mandatory for its citizens accompanied by sanctions for those who ignore it and nonmuslims are obliged to pay a social solidarity tax. Meanwhile, in Algeria, payments are made on a mandatory basis for private companies and voluntary for individuals. In addition, in the pattern of zakat distribution, the three countries distribute according to the guidance of the Qur'an (8 Asnaf) but have slight differences in the priority scale in which Indonesia prioritizes distribution to the poor, Sudan prioritizes the needs of each Mustahik and Muzakki is allowed to distribute to relatives as much as 20% of the obligatory zakat, meanwhile Algeria which prioritizes the poor, people in need and Fisabilillah. Then, the standard for the allocation of zakat social funds that may be taken as operational costs for nonprofit organizations handling zakat in the three countries is 12.5%.